2004
DOI: 10.1111/j.0953-816x.2004.03409.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activation of Ras regulates synaptic connectivity

Abstract: A synRas mouse model was used expressing constitutively activated Ha-Ras (Val12 mutation) in neurons to investigate the role of Ras-MAPkinase signalling for neuronal connectivity in adult brain. Expression of the transgene in the cortex of these mice starts after neuronal differentiation is completed and allows to directly investigate the effects of enhanced Ras activity in differentiated neurons. Activation of Ha-Ras induced an increase in soma size which was sensitive to MEK inhibitor in postnatal organotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
62
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 85 publications
7
62
0
Order By: Relevance
“…This modification is required for directing H-Ras to the neuronal membrane, where it mediates morphological changes and may participate in LTP and memory formation (16). Our studies indicate that in SST + neurons, DHHC9 is down-regulated by neuronal activity through a pathway that involves miR-134.…”
mentioning
confidence: 69%
“…This modification is required for directing H-Ras to the neuronal membrane, where it mediates morphological changes and may participate in LTP and memory formation (16). Our studies indicate that in SST + neurons, DHHC9 is down-regulated by neuronal activity through a pathway that involves miR-134.…”
mentioning
confidence: 69%
“…7,8 Ras also drives synaptic delivery of AMPARs [8][9][10][11] as well as production of dendritic protrusions/ spines. 12,13 In contrast, Rap typically favors However, a deeper analysis suggests another reason Plk2 may target multiple GAPs and GEFs, beyond the requirements of simple efficacy. RNA interference knockdown and overexpression experiments revealed that each Plk2 substrate actually affects relatively specific aspects of dendritic spine morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Mm (Martegani et al, 1992;Cen et al, 1993), contains both a CDC25 domain that confers exchange factor activity toward Ras (Cen et al, 1993;Wei et al, 1994) and a Dbl homology (DH)/plekstrin homology (PH) region that can act as an exchange factor for Rac1 (Kiyono et al, 1999) link the activation of Ras in general (Manabe et al, 2000;Arendt et al, 2004) and via Ras-GRF1 in particular (Krapivinsky et al, 2003;Schmitt et al, 2005) to molecular and cellular events, such as long-term potentiation and synaptic remodeling, which are thought to underlie memory. Genetic evidence, both from mouse models (Brambilla et al, 1997;Giese et al, 2001;Tian et al, 2004) and human disorders (Weeber et al, 2002), also supports such a link.…”
Section: Introductionmentioning
confidence: 99%
“…It is highly expressed at the synapses of neurons in the CNS (Sturani et al, 1997). There is considerable evidence to link the activation of Ras in general (Manabe et al, 2000;Arendt et al, 2004) and via Ras-GRF1 in particular (Krapivinsky et al, 2003;Schmitt et al, 2005) to molecular and cellular events, such as long-term potentiation and synaptic remodeling, which are thought to underlie memory. Genetic evidence, both from mouse models (Brambilla et al, 1997;Giese et al, 2001;Tian et al, 2004) and human disorders (Weeber et al, 2002), also supports such a link.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation